Antidiarrheal and Antisecretory Effect of 80% Hydromethanolic Leaf Extract of Moringa stenopetala Baker f. in Mice - Menbere Getaneh Woldeyohannes; Gelila Tamyalew Eshete; Alfoalem Araba Abiye; Abebe Ejigu Hailu; Solomon Assefa Huluka; Wondmagegn Tamiru Tadesse (Biochemistry Research International)
Introduction. In Ethiopia, different medicinal plants have been claimed and used to treat diarrheal diseases. However, these claimed effects for most medicinal plants have not been scientifically verified. One of such plants in Ethiopian folkloric medicine is Moringa stenopetala, which is usually consumed as a vegetable in southern Ethiopia. Thus, this study aimed to evaluate the antidiarrheal and antisecretory effects of 80% methanolic leaf extract of Moringa stenopetala in different mice models. Method. Using Swiss albino mice, castor oil-induced diarrhea, charcoal meal-based gastrointestinal motility, and castor oil-induced secretion models were employed to assess antidiarrheal activity. In all of the test models, animals were randomly assigned into five groups consisting of six animals in each group. Group I received 0.5 ml of the vehicle (2% tween-80), while group II was treated with standard drug (3 mg/kg loperamide) in the respective models, whereas groups III to V received 150, 300, and 450 mg/kg of the methanolic leaf extracts of Moringa stenopetala. Onset, frequency, consistency, and weight of stool (diarrhea) were recorded, and different parameters and percentage proportions were calculated. Data were analyzed using one-way ANOVA followed by Tukey’s test, and p < 0.05 was considered statistically significant at 95% confidence of interval. Result. In the castor oil-induced diarrheal model, the percentage inhibition of diarrhea was 48.5, 58.6, and 60% for the respective doses of 150, 300, and 450 mg/kg of the extract. And, the extract showed a 36.8, 54.4, and 55.9% reduction of peristalsis in charcoal meal-based gastrointestinal motility test compared to the negative control group. Moreover, in the antisecretory assay, the 150, 300, and 450 mg/kg doses of MEMS inhibited fluid contents of the stool by 11.5, 54.54, and 61.82%, respectively, relative to the vehicle-treated group. Conclusion. The findings revealed that the 80% methanolic leaf extract of Moringa stenopetala extract has shown antidiarrheal activity.